The Effects of Deposition Time on Phase and Structure of FeCoNi Films - Muhamad Mulyadi; Afrizal (Chemistry and Materials, 2022)
This study aims to determine the effects of deposition time on the phase and structure of FeCoNi. FeCoNi was prepared by electrodeposition method at room temperature. X-ray diffraction measurement shows the formation of a single phase of FeCoNi at 5 and 10 minutes of deposition, while at 20, 35, and 50 minutes, a new phase was formed, namely CoNi. The obtained FeCoNi and CoNi show a crystal plane at 2θ = 44.05° (111); 51.33° (002); and 75.59° (022) in all different deposition times, indicating the face centered cubic crystal structure. The effect of deposition time on the chemicals composition shows an anomalous co-deposition because Fe has a larger ratio than Co and Ni. The deposition rate and the value of current efficiency were found to be optimum at FeCoNi synthesized for 20 minutes, namely 0.00214 mg/cm2s and 97.00%.